Rapidly Progressing Refractory Hodgkin Lymphoma: A Case Report and a Possible Explanation - Ádám Jóna; Gábor Irsai; Sándor Barna; Gábor Méhes; Árpád Illés; László Váróczy (Case Reports in Medicine)
Introduction. Hodgkin lymphoma is a highly curable lymphoid malignancy; however treatment of a significant number of patients remains challenging. Case Report. The authors present an unusually rapidly progressing case of refractory advanced stage classical nodular sclerosis subtype Hodgkin lymphoma with unfavorable prognosis. A 66-year-old male patient was refractory for first-line doxorubicin, bleomycin, vinblastin, dacarbazine (ABVD) treatment with persistent disease; therefore physicians changed treatment for dexamethasone, cytarabine, and cisplatin (DHAP) and later ifosfamide, gemcitabine, and vinorelbine (IGEV) regimen. Unfortunately the patient developed acute kidney and respiratory failure and died after 6 months of treatment. Current and retrospective histological examination of the patient’s lymph node biopsy, skin lesion, and autopsy revealed the same aberrantly expressing CD4 positive nodular sclerosis subtype Hodgkin lymphoma. Conclusion. Aberrant expression of T-cell antigens on the Hodgkin and Reed/Sternberg cells could be associated with inferior outcome. T-cell associated antigens should be investigated more often in patients not responding sufficiently to treatment and hence treatment should be intensified or targeted therapy (brentuximab vedotin) should be considered.